A study on trust in E-commerce transaction by Malaysian consumer / Nor Farah Wahida Nasir and Norisma Shakilla Ismail - Nasir, Nor Farah Wahida; Ismail, Norisma Shakilla (Faculty of Business and Management, 2013)
According to Lawrence (2010) the number of internet users around the world has been steadily growing and this growth the impetus and the opportunities for global commerce. The growing popularity of internet business gives rise to their services that considered as more attractive services in e-commerce sector. The growing of e-commerce business gives chance to entrepreneur to take an opportunity to expand their business through internet. It will also influence the rises of transaction through internet. The growing of global commerce will affect the growing of internet business and e-commerce transaction in developing countries. Malaysia also affected from growing of global commerce. According to Hoffman (1999) and Jarvenpaa (2000), there is overwhelming evidence that trust in the online environment is an important element of electronic commerce (EC)relationships. According to Mayer (1995) and McKnight (2002), the overall trust in using E-commerce transaction is influenced by consumer’s perception of risk to the Ecommerce transaction due the nature of supporting infrastructure. Usually, the consumer’s perception of risk caused by their intention toward to perceived privacy, perceived security and company reputation. Despite the fears some consumers have about making online purchases, online purchasing behavior continues to grow in volume, and more and more people seem to be taking the plunge and buying online (Green, 2002; Horrigan, 2002). As the proportion of people refuse to buy online continue to shrink, concern about privacy, trust, security maybe overshadowed by other concerns. Ahuja et al. (2003) found privacy and security concern to be the most common reason their respondents gave for not shopping online, but other reasons were not behind on the list.